Waste Analysis and Characterization Study in a Philippine Science and Technology Research and Development Institution - Joven Barcelo; Maria Theresa Artuz; Myra Tansengco; David Herrera; Johnemma Mae Chuayana; Reynaldo Esguerra (Environment and Natural Resources Journal)
This paper presents the conduct of Waste Analysis and Characterization Study (WACS) in the Industrial Technology Development Institute of the Department of Science and Technology (DOST-ITDI) in Taguig City, Philippines. The study was produced following the introduction of 2020 guidelines developed by the Japan International Cooperation Agency for the Philippines to determine waste generation and generation rate per source, as well as waste composition, per capita generation, and bulk densities of the generated wastes. This then provided fundamental data in the formulation of initial plans and programs for the proper management of solid wastes in the institution. From the gathered results, DOST-ITDI generates 91.56 kg/day of solid waste during the dry season, and 77.54 kg/day during the wet season. The generated waste is composed of residuals for disposal (35.93% and 37.75%, dry and wet season), biodegradables (27.80% and 21.46%), and recyclables (22.54% and 28.95%). Per capita generation rates of 0.21 kg/capita/day (dry season) and 0.18 kg/capita/day (wet season) were also recorded. The research and development cluster of divisions was determined as a major contributor of waste at 42.37 to 57.62 kg/day. Bulk density values varied between waste fractions, with the main residuals for disposal components being the bulkiest at 29.27 to 32.90 kg/m3. The data collected from the study provided significant information useful in efforts to initiate programs for diversion of biodegradables, recyclables, and residuals-with further potential for recycling wastes, reducing residuals for disposal through proper segregation and recovery, and determining gaps and opportunities in plans, policies, and programs to improve solid waste management of the institution.